The issue of the technical competence for the social worker A questão da competência técnica para o assistente social - Jolinda de Moraes Alves (Semina: Ciências Sociais e Humanas, 1992)
This article deals with the social work "professional competence'", emphasizing its technical and political dimension. Concerning to the social role and the professionals insertion on the social-technical division of labor, situated on the services section of the current monopolist stage oh capitalism; the established knowledge of the social work within the welfare organizations, beginning with the attributions. instruments and techniques; the contradiction of a profession witch has employment links with organisms created by the State and by the Capital, but should give services lo subalternized users and the actual meeting of the social demand put in by the users and the issue of the professional obligation with the rupture of their condition ofpoverty and subordination. Este artigo trabalha a "competência profissional" do assistente social, enfatizando suas dimensões técnica e política. Para tanto contempla: o papel e a inserção da profissão na divisão sócio-técnico do trabalho, localizada no setor de serviços do atual estágio monopolista do capitalismo; o saber instituído do assistente social no interior das instituições de bem estar social a partir das suas atribuições, instrumentos e técnicas; a contradição de uma profissão que tem vínculos empregatícios com organismos criados pelo Estado e pelo Capital, mas que deve prestar serviços a usuários subalternizados; e o efetivo compromisso com o atendimento à demanda social colocada pelo usuário institucional.